Leadership Strategies In Building A Moral Culture And Facing Ethical Challenges In Madrasah Tsanawiyah - Annisa Tri Ananda Dewi; Muthi’ah Rahman; Hefniy Hefniy (International Journal of Instructional Technology, 2025)
This study aims to analyze how strategic leadership plays a role in the institutionalization of moral behavior and how the process of adaptation and ethical challenges are formed in a religious-based secondary education environment. The method used is a qualitative approach with a case study design through data collection techniques such as in-depth interviews, observation, and documentation. Data analysis is carried out through the stages of data condensation, data reduction, data display, and data verification to produce systematic findings. The results of the study indicate that strategic leadership is a major factor in the formation of an ethical culture through formal policies, daily habits, and a structured monitoring system. Ethical challenges arise from differences in student discipline levels, inconsistent implementation of rules, and the influence of the social and technological environment. On the other hand, student behavioral adaptation is formed through routine habits, teacher role models, and strengthening the internal social control system. The implications of this study indicate that the success of the formation of a moral culture is highly dependent on consistent leadership, the integration of values in the learning system, and the collaboration of all educational actors in building a sustainable and measurable ethical ecosystem within educational institutions.